Pelatihan Dan Pendampingan Tata Cara Pengurusan Jenazah Bagi Santri Pondok Pesantren El Hufadz Jombang - Qurrotul Ainiyah; Dita Dzata Mirrota; Mar'atul Azizah (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2023)
The purpose of this service is to describe the implementation of training and assistance on the procedures for managing corpses for Islamic boarding school students El Hufadz Jombang. The method of implementation is that prior to the implementation of training and assistance, a literature study is first carried out on various ways of organizing the funeral, preparation of tools and materials for the practice of organizing the funeral, determines the time of implementation and the duration of the community service activities together with the implementation team, determines and prepares the material to be delivered in community service activities. The results of this service are increasing community knowledge and understanding in organizing funerals, increasing community skills in organizing funerals so that it is possible for people to practice organizing funerals themselves in the village where they live. The factor that supports the implementation of this santi service activity is the amount of interest and enthusiasm of the participants during the activity, so that the activity takes place smoothly and effectively. The inhibiting factor is the limited training time.